Free trade or fair trade? How changes in the current international trade system could act as a development tool for third world countries : the Brazilian case : a thesis presented in fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Couto, Rossana Gabriely de Oliveira (Massey University, 2002)
This study analyses and discusses the impacts of fair trade on cooperatives in Brazil. It also addresses the debate on free trade, showing its weaknesses and strengths; and it acknowledges the importance of governments' macropolicies in promoting development though trade. This study supports the view that international trade, as practised today, is detrimental to the economies of Third World countries, and it suggests actions to overcome negative impacts of international trade. One of these suggestions is alternative trade. However, this study argues that alternative trade, although an efficient tool in promoting the interests of small farmers, poor communities, and unskilled workers, should not be substituted for mainstream trade. Instead, alternative trade should act as a complement and promote the interests of those who have been losing with trade liberalisation policies. In examining one of the alternatives to free trade (the fair trade movement) research was conducted in Brazil in 2001. The evidence from research shows that although fair trade is found in its initial stages in Brazil, the impact has been beneficial to those cooperatives involved with it. The research also found differences between rural and urban participants. Groups in a rural context shared same experiences and types of products (agriculture), while groups in an urban context shared different experiences and were involved in other types of products (manufactures). Although all groups shared some similar difficulties, rural groups were more disadvantaged in terms of the distance, lack of infrastructure, communication problems, and lack of access to services. This study concludes that although the fair trade movement is still in its initial stages in Brazil and has had minor macroeconomic impacts on the Brazilian economy, it should be encouraged since it creates opportunities for marginalised groups to sell their production and reach a minimum standard of living. The study also argues that both alternative and mainstream trading system have their strengths and weaknesses, and that the ideas behind alternative trade should be incorporated into the mainstream trading system in order to make it fairer to all participants.
Keywords: Community development; Producer cooperatives; Economic policy; Economic conditions; Free trade; Competition; Brazil